Evaluation of Candidate Teacher Training Process from the Viewpoint of Mentor Teachers - Alabaş, Ramazan; Yılmaz, İhsan (Redfame Publishing, 2018)
Teacher education has been one of the most debated topics in history of Turkish education. At the beginning of the teacher's career, the Turkish Ministry of National Education (MONE) implemented the Candidate Teacher Training Program in 2016, so the teachers accepted to the profession were qualified as “candidate teachers” and they were subjected to the training process. The aim of this research is to examine the opinions of the mentor teachers regarding the Candidate Teacher Training Program implemented by the Turkish MONE for the training of candidate teachers. This research, which is a qualitative case study, was conducted with the participation of 36 teachers who are mentors to candidate teachers within the Candidate Teacher Training Program in the schools, which were affiliated to MONE in Kastamonu province center and its districts. The data of the study were collected by means of a semi-structured interview form. The data obtained in the research were analyzed with descriptive analysis and content analysis approaches. Mentor teachers thought that the Candidate Teacher Training Program is beneficial because the program provided the candidate teachers with the opportunities to identify students, acquire educational-instructional competence, acquire managerial knowledge, and identify the school and the social environment. However mentor teachers stated that they have experienced some problems related to the process such as filling in forms, some problems resulting from the candidate teacher, and time inadequacy.
Keywords: 4. Education; 16. Peace & justice